Impact of inflammatory markers in diabetic SARS-CoV-2 critically ill patients - Saiqa Rasool Shah; Shaheen B Shaikh; Greeshma B. Kotian; Haji Mohammed Ismail; Ganesh Prasad V; Shaheena Yassir (Al Ameen Medical College, 2023)
Introduction: Covid patients have elevated inflammatory markers especially in those with comorbid conditions like diabetes. The study aimed to compare the inflammatory response in critically ill SARS CoV-2 diabetic and non-diabetic subjects admitted in ICU. Methodology: A retrospective data collection study was conducted on113 critically ill SARS CoV-2 patients admitted in ICU. The data of C-reactive protein, ferritin, LDH, RBS and glycated hemoglobin were collected from laboratory. The duration of stay, diabetic and mortality status were collected from electronic repository of the hospital. Independent 't' test and Mann Whitney U test were used for parametric and non-parametric data respectively to compare the study groups. Chi-square analysis done for categorical variables. Spearmann correlation was used to correlate inflammatory markers with HbA1c. Results: Serum ferritin, LDH and CRP was elevated in diabetic population and was found to be statistically significant with CRP (p value 0.034). Duration of stay in hospital was reduced in diabetes (p value 0.033). Positive correlation of HbA1c was seen with CRP and LDH but found to be statistically significant only with CRP (r = 0.179, p = 0.040). Conclusion: Study concluded that inflammatory markers CRP, ferritin and LDH were comparatively elevated in diabetic versus non diabetic SARS CoV-2 patients.